Analysis of Individual and Work-Related Factors Towards MSDs in Cement Transporters - Ratna Anindir Ipa Hoy Purandima; Anderias Umbu Roga; Johny A.R Salmun (Lontar : Journal of Community Health, 2023)
Musculoskeletal Disorders (MSDs) occur in skeletal muscles that are felt by someone, which is usually characterized by pain in body parts while working. The World Health Organization (WHO) states that the prevalence of MSDs is almost 60% of all occupational diseases. MSDS generally occur due to occupational factors and individual factors. Cement transporter activities while doing their work have the potential to experience MSDs complaints. The purpose of this study was to determine the relationship between age, BMI, duration of working hours, and work posture at the cement transporter at PT. Cipta Sarana Pembangunan Kupang.This research is an analytic survey with a cross-sectional approach conducted from September to October 2021. The population in this study is 40 people who carry semen. Data collection using the Nordic Body Map questionnaire and work posture data using the REBA (Rapid Entire Body Assessment) method. Data analysis used the Chi-Square test to determine the relationship between individual and occupational factors on MSDs complaints. The results showed that there was no relationship between age and p-value (0.657), and there was a relationship between IMT, duration, and work posture with p-value (0.006), (0.038), and (0.003). It is expected that cement transport workers will prevent the occurrence of Musculoskeletal Disorders (MSDs) complaints by taking advantage of rest periods and adopting a healthy lifestyle. In addition, the company should provide training and education about work postures that are ergonomic concepts.